Nano- and micro-scale techniques for electrical transport measurements - Williams, B (2016)
This thesis outlines the development of two new techniques that exploit very small structures, on the micro- and nano-scale, to enable innovative electrical transport measurements on a variety of materials of current interest in condensed matter physics. The first technique aims to apply the versatility of electron-beam lithography for micro-fabrication of patterned electronic circuitry to the problem of performing transport experiments on individual crystallites taken from a typical powder sample. We show that these small samples, tens of microns in size, are actually often very high quality single crystals and can be exploited for measurements of electrical transport in materials of which no larger crystals are available. By way of demonstration, we present the results of preliminary transport measurements on a crystallite of the layered oxide chalcogenide Sr2MnO2Cu1.5Se2. We report a phase transition in the resistivity at 213K which may correspond to the onset of previously reported short-range order in copper and vacancy sites in the Cu1.5Se2 planes. The second technique is designed to investigate the topological protection of surface transport in 3-D topological insulators. We decorate the surfaces of single-crystal samples with two different species from a well-characterised family of single-molecule magnets. The two coatings have an electrostatically identical influence on the sample surface, but differ in that one species carries a spin and the other is spinless. The spinless molecule acts as a control, to allow us to cleanly determine the influence of the magnetic component of a scattering potential on transport in the surface. With this technique we investigate proposed topological Kondo insulator SmB6. We find that the surface state dominates low-temperature transport and demonstrate that the momentum relaxation is very sensitive to a spin degree of freedom in the scatterer, in keeping with expectations of a topological insulator.